Efficacy-oriented compatibility for component-based Chinese medicine - Zhang, Jun-hua; Zhu, Yan; Fan, Xiao-hui; Zhang, Bo-li (Acta pharmacologica Sinica, 2015)
Single-target drugs have not achieved satisfactory therapeutic effects for complex diseases involving multiple factors. Instead, innovations in recent drug research and development have revealed the emergence of compound drugs, such as cocktail therapies and ＂polypills＂, as the frontier in new drug development. A traditional Chinese medicine （TCM） prescription that is usually composed of several medicinal herbs can serve a typical representative of compound medicines. Although the traditional compatibility theory of TCM cannot be well expressed using modern scientific language nowadays, the fundamental purpose of TCM compatibility can be understood as promoting efficacy and reducing toxicity. This paper introduces the theory and methods of efficacy-oriented compatibility for developing component-based Chinese medicines.